Literasi Informasi Dan Peran Perpustakaan Dalam Meningkatkan Sdm - Umir Rodliya (IAIN Ponorogo, 2011)
The advance of a state is decided by the human resources,particularly the information competence. Libraries have animportant role to increase this resource by improving the societyliteracy. Endeavor to upgrade the competence of information literacywould produce the strength of information competency, namely thecompetence to empower to intensifying their daily activity. So thatit can influence and accelerate societ